USE OF A JUST IN TIME TEACHING / FLIPPED CLASSROOM QUESTIONNAIRE FOR THE DETECTION OF IMPROVEMENTS IN UNIVERSITY EDUCATIONAL MATERIALS - Vas, Juan Ángel Contreras; Andrade, Malena G. Melo; Masa, Juan Arias; Vasco, y Juan Ramón Moya (IJRDO- Journal of Educational Research, 2017)
With this experimental research, we try to detect the possibility of improving theeducational materials used in university teaching. The creation and improvement ofeducational materials go through several stages such as: defining contents to be taught,selecting sources of information, process materials, make the information available to thestudents, be studied by them, check the assimilation, to detect defects of assimilation,improvement of materials and, to verify that the improvement made generates the appropriateeffects on students. This article demonstrates the realization of an experiment of detection,improvement and verification of that improvement of some university educational materials.To carry out the task, we use questionnaires like Just in Time Teaching / Flipped Classroomto obtain information from the students, and the use of mixed methodologies for the detectionof materials to improvement and verification of the effects that has had the improvement inthe application of the same.